2017
DOI: 10.1103/physrevlett.119.017701
|View full text |Cite
|
Sign up to set email alerts
|

Robust Single-Shot Spin Measurement with 99.5% Fidelity in a Quantum Dot Array

Abstract: We demonstrate a new method for projective single-shot measurement of two electron spin states (singlet versus triplet) in an array of gate-defined lateral quantum dots in GaAs. The measurement has very high fidelity and is robust with respect to electric and magnetic fluctuations in the environment. It exploits a long-lived metastable charge state, which increases both the contrast and the duration of the charge signal distinguishing the two measurement outcomes. This method allows us to evaluate the charge m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 40 publications
0
73
1
Order By: Relevance
“…To this end, we consider the harmonic heterostructure confinement, Eq. (14). In this case, the full three-dimensional model has an analytical solution for arbitrary magnetic field (see Appendix B), which we can use as a benchmark for the effective two-dimensional model.…”
Section: Accuracy Of the Perturbative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we consider the harmonic heterostructure confinement, Eq. (14). In this case, the full three-dimensional model has an analytical solution for arbitrary magnetic field (see Appendix B), which we can use as a benchmark for the effective two-dimensional model.…”
Section: Accuracy Of the Perturbative Resultsmentioning
confidence: 99%
“…9 This, so far missing, spectroscopic tool is essential for a quantitative assessment of, for example, the spin-orbit fields, 10 or the hyperfine electron-nuclear interaction, and the related limits on the spin relaxation, 11,12 dephasing, 13 or measurement fidelities. 14 To illustrate the power of these tools, we use them here to fit the strengths of the spin-orbit interactions in a GaAs quantum dot. We find excellent agreement with values extracted from an independent fit based on the directional variation of the spin relaxation time done in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then combined with MW bursts, Koppens et al demonstrated the first driven coherent single spin rotations in 2006 [45]. Furthermore, the visibility of readout in the singlet-triplet basis can be enhanced by charge state latching [46,47] and intermediate excited states [48]. In Harvey-Collard et al's work, they achieved a measurement fidelity as high as 99.86% via charge state latching, and in 2018, Fogarty et al demonstrated measuring a spin-1/2 qubit using this new method [49].…”
Section: Spin-1/2 Qubitmentioning
confidence: 99%
“…In this article we are concerned with the effects of the in-plane magnetic field on the spin, rather than orbital, structure of the states. Such an analysis requires 5 We note that the name and interpretation of the quantity Φ is motivated by the form of Eq. (16).…”
Section: Spin-dependent Perturbationsmentioning
confidence: 99%